The Minimum Core Obligations of Economic, Social, and Cultural Rights : The Rights to Health and Education - Shields, Kirsteen (World Bank, Washington, DC, 2018)
Economic, social, and cultural rights (ESCR), such as the right to education and the right to health, comprise one of the two principal pillars of the United Nation (UN) human rights framework - the other pillar of which is constituted of civil and political rights (CPR); together with the UDHR, these two groups of rights comprise the international bill of rights. ESCR also overlap substantially with development activities, in that they share significant subject matter coverage. Put differently, development activities now occupy many areas governed by ESCR. ESCR are also central to conflicts over resource allocation which increasingly arise in both developed and developing countries as a result of crises stemming from climate change, violent conflict, and war and displacement. In such resource, constrained contexts, ESCR, and minimum core doctrine (MCD) in particular, provide a potential means to prioritize resource allocation through the identification of minimum core obligations (MCOs).